Numerical Approximation of Periodic Solutions of van der Pol's Equation - Greenspan, Donald (University of Wisconsin-Madison Department of Computer Sciences, 1970)
Two new discrete methods, one based on discrete mechanics, the other based on high-order Taylor series, are developed and applied to approximate periodic solutions of van der Pol's equation. Typical numerical results are exhibited from a broad spectrum of values of in the range of physical interest.